Smernice evropeizacije upravnega procesnega prava - Kovač, Polonca (Javna uprava, 2017)
The Europeanisation of public administration and administrative processes is a continuous phenomenon, driven by the harmonisation in regulation and implementation of fundamental administrative law principles as developed by the Council of Europe and EU. The article provides an analysis of general European administrative principles within the context of the good administration doctrine as a value-based framework of Europeanisation in the field of protection of public interest and the rights of the parties in administrative matters at the national level. It presents the main guidelines, sources and consequent trends of Europeanisation, such as redefinition and extension of the ratio of administrative procedures, the various approaches to codification. It is emphasised that administrative affairs should be resolved in a more transparent and participative way. The author concludes that Europeanisation, as a continuous convergence process, should be seen as a - albeit formally non-binding - framework and potential also in Slovenia, thus enabling a pro-active co-shaping of the European Administrative Space.
Keywords: administrative procedure law; Europeanisation; evropeizacija; evropsko pravo; fundamental principles; procesno pravo; smernice razvoja; temeljna načela; trends; upravno pravo